Women Artists and their Work as a Subject of Exhibition Reviews in Latvia: The 1840s–1915 - Vanaga, Baiba (Kunstiteaduslikke uurimusi, 2018)
Starting at the beginning of the nineteenth century, women from Latvia actively sought opportunities to study art and participated in the local and international art scene. Although the dominant view was that women were more limited in their creative abilities than men, their involvement in art was generally accepted. Nevertheless, a significant part of society believed, and publicly expressed the opinion, that women artists were patient, endowed with taste and good at copying nature, but that they could not create outstanding works of art, and therefore they should be judged by other (lower) criteria than those applied to male artists. This article discusses the most vivid reviews that were published by critics about women artists and their creative abilities from the 1840s until 1915. These examples reveal typical trends and stereotypes of the era with respect to women artists and their work.